The future is but a word - Emília Araújo; Bárbara Guimarães (Temporalités)
Today, scientific research is seen as being largely dominated by the short-term, and by the constant need to gain legitimacy in the eyes of society. This text analyzes the existing literature on the concept of future and seeks to explore some of the main meanings it has for scientists. Based on interviews with researchers working on different projects in Portuguese research centers, the authors scrutinize some of the implications of the recurrent reference to the future in their research agendas. Starting with a review of the literature on the relations between science, time, and future, they show that nowadays, scientists experience some difficulty when dealing with the long-term in science, mostly due to the pressure of the market on innovation. In view of their profiles and discourses, what must be stressed are the risks and challenges playing out in the conflict between the short and the long term in scientific research.